2015
DOI: 10.1080/00207543.2015.1073402
|View full text |Cite
|
Sign up to set email alerts
|

Optimal production and inventory decisions under demand and production disruptions

Abstract: Unanticipated events may take place and disrupt demand and/or production in a supply chain. Conditional on the type, magnitude and duration of disruptions, changes may be called to revise the original production plan. We analyse different disruption scenarios and propose optimal production-inventory models for products facing demand and production disruptions. To lower the cost, we optimise the production run time, purchasing times and order quantity for the manufacturer. Numerical experiments are conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The authors discovered that the optimal decision value after the demand interrupt is a linear function of the demand interrupt and the optimal decision value before it. [49] investigated the problem of model selection in a cooperating system under cap-and-trade regulation with demand disruptions. The authors first determined optimal decisions in the absence of demand disruption and then introduced demand disruption.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors discovered that the optimal decision value after the demand interrupt is a linear function of the demand interrupt and the optimal decision value before it. [49] investigated the problem of model selection in a cooperating system under cap-and-trade regulation with demand disruptions. The authors first determined optimal decisions in the absence of demand disruption and then introduced demand disruption.…”
Section: 2mentioning
confidence: 99%
“…Our model is similar to that those in [50] and [49] since all of the proposed models examine a selection decision when one of the two components has no value in the absence of the other. Following [50], we thus set the product, service (for independent mode only), and bundle (for bundling mode only) prices separately in our model.…”
Section: 2mentioning
confidence: 99%
“…Chowdhury and Quaddus (2016) identified that supply chain flexibility and disaster preparation have the highest importance for supply chain readiness, whilst recovery capability has the highest importance to response-recovery. In addition, studies by He et al (2016) and Xu et al (2016) have considered the impact of the reliability of suppliers on supply disruptions. He et al (2016) propose the application of reliability threshold values on buyer pricing and ordering decisions, while Xu et al (2016) build a flexibility production-inventory model to balance the demand and production disruptions.…”
Section: Reliability and Supply Disruptionmentioning
confidence: 99%
“…In addition, studies by He et al (2016) and Xu et al (2016) have considered the impact of the reliability of suppliers on supply disruptions. He et al (2016) propose the application of reliability threshold values on buyer pricing and ordering decisions, while Xu et al (2016) build a flexibility production-inventory model to balance the demand and production disruptions.…”
Section: Reliability and Supply Disruptionmentioning
confidence: 99%
“…The plant location decision has often been formulated as a cost optimization problem by converting the associated decision attributes into monetary values. This cost optimization model usually involves decision making regarding the following attributes: market demand, production and storage capacity, production cost, and supply reliability [6][7][8][9][10][11][12]. This optimization model has been extended by incorporating uncertainty-variation of population, changeable market trends, and unpredictable demand-into the decision-making process [13].…”
Section: Introductionmentioning
confidence: 99%